Factors Influencing Nutritional Status in The Region Work of Wiyega District Health Center Pani - Aplena H Gane; Nur Al-faida; Bau Kanang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Malnutrition in children under 5 years old is a condition when the child's weight is below the moderate range. Objective: to determine the factors that influence the incidence of malnutrition in toddlers aged 6-59 months in the Wiyega Health Center Working Area, Paniai Regency. Method: The type of research is quantitative with analytical observational cross-sectional approach. The population taken using total sampling of 30 samples who experienced malnutrition at the Wiyega Health Center, Paniai Regency. Data analysis using the computer release program (SPSS) version 16.0 and using chi square. Results: There is a relationship between the level of maternal employment and the incidence of malnutrition with a p-value of 0.00 (<0.05), there is a relationship between the level of maternal education and the incidence of malnutrition with a p-value of 0.00 (<0.05), there is a relationship between the level of maternal knowledge and the incidence of malnutrition with a p-value of 0.01 (<0.05) and there is a relationship between exclusive breastfeeding and the incidence of malnutrition. Conclusion: Based on the results of the study, it was concluded that there is a relationship between maternal employment, education, knowledge, exclusive breastfeeding and the incidence of malnutrition. Suggestion: To be input for mothers who have toddlers aged 6-59 months to be able to increase knowledge and be aware of the importance of paying more attention to toddlers regarding the nutritional intake they receive.